The psychological well-being of children orphaned by AIDS in Cape Town, South Africa. - Cluver, L; Gardner, F (BioMed Central, 2006)
BACKGROUND: An estimated 2 million children are parentally bereaved by AIDS in South Africa. Little is known about mental health outcomes for this group. METHODS: This study aimed to investigate mental health outcomes for urban children living in deprived settlements in Cape Town. 30 orphaned children and 30 matched controls were compared using standardised questionnaires (SDQ) on emotional and behavioural problems, peer and attention difficulties, and prosocial behaviour. The orphan group completed a modified version of a standardised questionnaire (IES-8), measuring Post-Traumatic Stress symptoms. Group differences were tested using t-tests and Pearson's chi-square. RESULTS: Both groups scored highly for peer problems, emotional problems and total scores. However, orphans were more likely to view themselves as having no good friends (p = .002), to have marked concentration difficulties (p = .03), and to report frequent somatic symptoms (p = .05), but were less likely to display anger through loss of temper (p = .03). Orphans were more likely to have constant nightmares (p = .01), and 73% scored above the cut-off for Post-Traumatic Stress Disorder. CONCLUSION: Findings suggest important areas for larger-scale research for parentally-bereaved children.